Purification and Characterization of a Thermo- and pH-Stable Laccase From the Litter-Decomposing Fungus Gymnopus luxurians and Laccase Mediator Systems for Dye Decolorization - Sun, Yue; Liu, Zi-Lu; Hu, Bo-Yang; Chen, Qing-Jun; Yang, Ai-Zhen; Wang, Qiu-Ying; Li, Xiao-Feng; Zhang, Jia-Yan; Zhang, Guo-Qing; Zhao, Yong-Chang (Frontiers in Microbiology, 2021)
An extracellular laccase (GLL) was purified from fermentation broth of the litter-decomposing fungus Gymnopus luxurians by four chromatography steps, which resulted in a high specific activity of 118.82 U/mg, purification fold of 41.22, and recovery rate of 42.05 %. It is a monomeric protein with a molecular weight of 64 kDa and N-terminal amino acid sequence of AIGPV TDLHI, suggesting that GLL is a typical fungal laccase. GLL demonstrated an optimum temperature range of 55-65 ℃ and an optimum pH 2.2 towards 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). It displayed considerably high thermostability and pH stability with about 63% activity retained after 24 h at 50 ℃, and 86% activity retained after 24 h at pH 2.2, respectively. GLL was significantly enhanced in the presence of K+, Na+, and Mg2+ ions. It demonstrated Km of 539 µM and kcat / Km of 140 mM-1·s-1 towards ABTS at pH 2.2 and 37 ℃. Acetosyringone (AS) and syringaldehyde (SA) were the optimal mediator of GLL (0.4 U/mL) for dye decolorization with decolorization rate of about 60-90% towards eleven of the fourteen synthetic dyes. The optimum reaction conditions were determined to be mediator concentration of 0.1 mM, temperature range of 25-60 ℃, and pH 4.0. The purified laccase was the first laccase isolated from genus Gymnopus with high thermostability, pH stability, and effective decolorization towards dyes, suggesting that it has potentials for textile and environmental applications.